The pot, the cup and the jar: Coming together in/for stories - İnce Şengül (Cultural Science)
What sort of story can you tell with just a pot, a cup, a coffee pot, a jar, a chopping board, an onion and a knife? Would the stories told among a group of seven PhD candidate women reveal the burden of writing a PhD dissertation relating the process to cooking? We, eight women, came together to run an event for the March 8th, International Women’s Day in 2014 and talked about what we had been experiencing during the period of writing master’s and PhD dissertations through the help of some ordinary life kitchen objects. We called this digital storytelling workshop, “I have food on the stove”, getting our inspiration from a very common phrase used by women during their everyday life conversations in Turkey. This workshop enabled me to think about what kind of roles both kitchen and objects have in our lives and how telling stories help women to deal with hard times.